Phenotype in parkinsonian and nonparkinsonian LRRK2 G2019S mutation carriers - Marras, C. (Lippincott Williams & Wilkins, 2011)
OBJECTIVES: Using a family study design, we describe the motor and nonmotor phenotype in probands with LRRK2 G2019S mutations and family members and compare these individuals to patients with idiopathic Parkinson disease (iPD) and unrelated controls. METHODS: Probands with G2019S mutations and their first-degree relatives, subjects with iPD, and unrelated control subjects were identified from 4 movement disorders centers. All underwent neurologic examinations and tests of olfaction, color vision, anxiety, and depression inventories. RESULTS: Tremor was more often a presenting feature among 25 individuals with LRRK2-associated PD than among 84 individuals with iPD. Subjects with LRRK2-PD had better olfactory identification compared with subjects with iPD, higher Beck Depression Inventory scores, and higher error scores on Farnsworth-Munsell 100-Hue test of color discrimination. Postural or action tremor was more common among 29 nonmanifesting mutation carriers compared with 53 noncarriers within the families. Nonparkinsonian family members had higher Unified Parkinson's Disease Rating Scale motor scores, more constipation, and worse color discrimination than controls, regardless of mutation status. CONCLUSIONS: Although tremor is a more common presenting feature of LRRK2-PD than iPD and some nonmotor features differed in degree, the phenotype is largely overlapping. Postural or action tremor may represent an early sign. Longitudinal evaluation of a large sample of nonmanifesting carriers will be required to describe any premotor phenotype that may allow early diagnosis.